The Role of Iron in Advanced Oxidation Technologies: A Review of Applications in Wastewater Remediation - Muhammad Saad Ashraf; Samra Kanwal; Faryal Zafar; Iqra Zahoor; Mubashar Hussain Ch; Sabika Nasir; Rania Safdar; Dawood Ali; Ali Khan Yousaf Zai (Indus Journal of Bioscience Research, 2025)
Iron-based catalysts have emerged as pivotal components in advanced oxidation technologies (AOTs), offering effective and sustainable solutions for the remediation of contaminated wastewater. This review provides a comprehensive overview of the multifaceted role of iron in various AOTs, including Fenton, photo-Fenton, electro-Fenton, and heterogeneous catalytic processes. Emphasis is placed on the mechanisms of reactive oxygen species (ROS) generation facilitated by iron, the influence of operational parameters, and the impact of iron speciation and redox cycling. Additionally, the review discusses recent advances in iron-modified materials, such as iron oxides, iron-doped nanomaterials, and iron-supported catalysts, highlighting their enhanced catalytic performance and reusability. Challenges related to sludge generation, iron leaching, and system scalability are critically analyzed, alongside proposed strategies for optimization and integration into existing wastewater treatment frameworks. By synthesizing current research and technological developments, this article underscores the central role of iron in advancing efficient, cost-effective, and environmentally friendly wastewater remediation methods.